LCu(μ-X)2CuL compounds: An induced cuprophilic interaction. (25th September 2016) - Chen, Peter E.; McNeely, James; Lum, June S.; Gardner, Evan J.; Phillips, Val; Golen, James A.; Rheingold, Arnold L.; Doerrer, Linda H.
Graphical abstract: Four new [LCu(I)X] compounds have been prepared, one of which is noticeably folded. The faint cuprophilic interaction does not cause the fold, but rather the varying O–Cu electrostatic interactions control the fold, and when the dimer fold angle is narrow enough, the two Cu atoms can interact in a metallophilic fashion. Abstract: A trio of dimeric copper(I) complexes of the formula [(Ph3 P)Cu(μ-X)2 Cu(PPh3 )] (X = OC6 F5, 1, OC4 F9, 2, OCPh(CF3 )2, 3 ) were prepared and characterized by X-ray crystallography, elemental analysis, and NMR spectroscopy ( 1 H, 13 C, 19 F, 31 P), as was the monomeric [(cy3 P)Cu(OC4 F9 )] (cy = cyclohexyl, 4 ). Solution conductivity studies demonstrate that all three new dinuclear compounds, as well as the known [(Ph3 P)Cu(μ-OC4 H9 )2 Cu(PPh3 )], 2-H, are neutral species in solution and do not rearrange into ion pairs. The fold angle ( β ) varies among these four dimers and the Cu(I)⋯Cu(I) distance in the structure of2, 2.8315(5) Å, is cuprophilic. The Cu(I)⋯Cu(I) distances for1, 2-H, and3 are 3.0533(5), 2.890(2), and 3.0169(6) Å respectively. Density functional theory (DFT) calculations were performed on1, 2, 3, and2-H, as well as the hypothetical1-H, and several related models. Five PMe3 models, 1 (Me ), 1-H (Me ), 2 (Me ), 2-H (Me ), and3 (Me ) were also studied as well as five monomers [(Me3 P)CuX]1-mon, 1-H (mon ), 2-mon, 2-H (mon ), and3-mon to understand the electronic reasons for folding in this group of compounds. A Natural Energy Decomposition Analysis (NEDA) indicates that electrostatic stabilizations are the dominant factor governing the strength of interaction between monomeric fragments in1 (Me )–3 (Me ). NBO analysis reveals that1 (Me ) and1-H (Me ) do not display any cuprophilic interactions. The folding angle observed in2 (Me ), 2-H (Me ), and3 (Me ), which is correlated with an increased delocalization from the oxygen 2 pz lone pairs, brings the metal centers into sufficient propinquity to have weak Cu⋯Cu orbital interactions. Weak luminescence behavior at room-temperature is also consistent with these assignments.